Hydrodynamics and mass transport in wall tube and microjet electrodes. 1. Finite element simulations - Melville, J; Simjee, N; Unwin, P; Coles, B; Compton, R (2002)
We report a general numerical strategy for the simulation of the hydrodynamics and mass transfer at a wall tube electrode based on finite element modeling. Previous empirical and approximate analytical treatments predicting the current as a function of flow rate and cell geometry are critically assessed and shown to have limited general applicability. Good agreement between experiment and simulation is found, providing a rigorous basis for future work with these electrodes.